Electrospun nanofibres containing Zn-MOF for electrochemiluminescent determination of fenpropathrin residues in fruit juices. (30th March 2023) - Sun, Zhuo; Lu, Juan; Zhang, Xin; Shan, Xiangyu; Wu, Qian; Li, Chao; Li, Huiling; Yang, Shuning; Tian, Li
Highlights: ECL sensor for detection of fenpropathrin residue was developed for the first time. ECL sensor was constructed based on Zn-MOF fibres, CdTe and Au@Pt-rGo. Zn-MOF fibres were the carrier of CdTe and Au@Pt-rGo. Zn-MOF fibres were the co-reaction promoter of Ru(bpy)3 2+ /tri- n -propylamine system. Abstract: In this work, Zn-MOF electrospun nanofibres (Zn-MOF NFs), CdTe and Au@Pt-rGo were applied to Ru(bpy)3 2+ /tri- n -propylamine electrochemiluminescence (ECL) system. And a novel ECL sensor for the determination of fenpropathrin was constructed for the first time. Due to the large surface area and pores, Zn-MOF NFs can both carry CdTe and Au@Pt-rGo and promote luminescence by facilitating electron transfer and reducing electron transport paths. CdTe participated in the luminescence reaction and improved the system's sensitivity together with Ru(bpy)3 2+ . Au@Pt-rGo can promote electron transport in the system. Under the synergistic effect of the three, the ECL sensor had achieved satisfactory results in weak alkaline solution. The constructed ECL sensor can detect fenpropathrin in the range of 4 × 10 −11 –4 × 10 −6 M, and the detection limit was 1.33 × 10 −11 M (S/N = 3). It can be used to detect fenpropathrin in juice samples, which provided a new idea for determining fenpropathrin.